Enhancing System Capacity Through Joint Space‐Ground Multi‐Beam Coordination for LEO Satellite Systems - Yuyang Liu; Tong Shi; Hua Wang (Engineering Reports)
ABSTRACT Due to the long transmission distance of the constellation network represented by the low‐orbit satellite system, the satellite‐to‐ground link is subject to large path loss and limited communication performance. This paper uses multi‐satellite and multi‐beam joint transmission technology to form a virtual multiplex network with ground multi‐antenna terminals (Multiple‐Input Multiple‐Output [MIMO] system). However, due to the high‐speed movement of satellites, the topology of the MIMO system is unstable, which in turn affects the stability of the system throughput. This article proposes two inter‐satellite cooperation modes to improve the stability of MIMO system capacity. The first method is to optimize the channel capacity by rationally allocating the beam power of the gateway station so that the gateway station can achieve transparent forwarding through satellites. The second method rotates the angle of the user's receiving antenna to combat channel changes caused by changes in satellite position. Simulation results show that both methods can effectively improve the minimum channel capacity. Transparent forwarding can increase the capacity by about 22.7%, while the rotating antenna can still improve the performance gain by at least 36.3% even with a limited rotation angle. This research contributes to the development of stable and efficient communication systems in satellite‐ground cooperative networks.